(untitled) (Baltic Journal of Sport and Health Sciences, 2024)
Purpose: The study aimed to evaluate the association between maternal emotional intelligence and coping strat[1]egies with diabetes management in adolescents diagnosed with type 1 diabetes. Design and Methods: A cross-sectional study was conducted with mothers of adolescents (aged 12–17 years) with type 1 diabetes (n = 75). Data collection instruments included the Trait Emotional Intelligence Question[1]naire-Short Form (TEIQue-SF) and the Brief COPE, alongside a structured questionnaire covering diabetes man[1]agement and sociodemographic factors. The primary outcome measure of diabetes management was glycosylated hemoglobin (HbA1c) levels. Data were collected via both paper-based questionnaires and an online survey in 2023. Results: Mothers of adolescents with optimal diabetes control exhibited significantly higher scores in the so[1]ciability dimension of emotional intelligence compared to those whose children had suboptimal diabetes control (p = 0.029). No statistically significant association was found between coping strategies and diabetes management in adolescents with type 1 diabetes (p > 0.05). However, maternal emotional intelligence was positively correlated with both problem-focused (rho = 0.669, p < 0.001) and emotion-focused coping strategies (rho = 0.321, p = 0.005), while lower emotional intelligence was significantly associated with avoidant coping (rho = -0.434, p < 0.001). Conclusions: The sociability dimension of maternal emotional intelligence was positively associated with opti[1]mal diabetes management in adolescents with type 1 diabetes. Higher maternal emotional intelligence predicted the use of adaptive coping strategies, specifically problem-focused and emotion-focused coping, whereas lower emotion[1]al intelligence was linked to avoidant coping strategies. Practical Implications: Interventions aimed at enhancing the sociability aspect of emotional intelligence in mothers may improve their social functioning and, consequently, facilitate better diabetes management in their ado[1]lescent children. Keywords: type 1 diabetes, emotional intelligence, coping strategies, diabetes management.